EFEKTIVITAS PENGGUNAAN SIMULASI PHET TERHADAP HASIL BELAJAR SISWA PADA MATERI ASAS KONTINUITAS DI SMA NEGERI 1 LIKUPANG - Rumimpunu, Fira F. N; Londa, Treesje K; Polii, Jeferson; Lolowang, Jimmy (SOSCIED, 2024)
This research aims to determine the effectiveness of student learning outcomes using PhET simulation material on the principle of continuity for class XI students at SMA Negeri 1 Likupang. This research uses an experimental method with a Two Group design using Post-test Control Group Design. The sample for this research was taken from class XI MIA 1 as an experimental class which was taught using PhET Simulation with a total of 20 students and class The second class is homogeneous and equal. The data taken in this study came from the same post-test in both classes. The average post-test score for the experimental class was 87.35 and the post-test for the control class was 70.7, which means that student learning outcomes in the experimental class were higher than student learning outcomes in the control class. The research results were analyzed using the t-test with a significance level of 0.05, obtaining a value of tcount = 7.763 > ttable = 1.686, so H0 was rejected and H1 was accepted. Meanwhile, for the N-Gain Test, the percent obtained was 76, which is within the effective criteria. From the results of this research it can be concluded that the use of PhET simulations is effective on student learning outcomes in material as continuity.